2014
DOI: 10.1152/ajpheart.00977.2012
|View full text |Cite
|
Sign up to set email alerts
|

Nox-derived ROS are acutely activated in pressure overload pulmonary hypertension: indications for a seminal role for mitochondrial Nox4

Abstract: Pulmonary arterial hypertension is a severe progressive disease with marked morbidity and high mortality in which right ventricular (RV) failure is the major cause of death. Thus knowledge of the mechanisms underlying RV failure is an area of active interest. Previous studies suggest a role of NADPH oxidase in cardiomyocyte dysfunction in the left heart. Here we postulate that acute pressure overload induced by pulmonary artery banding (PAB) leads to a Nox4-initiated increase in reactive oxygen species (ROS) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 43 publications
(67 reference statements)
1
55
0
Order By: Relevance
“…3, D and E). Interestingly, Nox4 protein has been reported to localize to the mitochondria in the right ventricles of a mouse model of pressure overload pulmonary hypertension (14) and in breast epithelial cells (17). These data suggest the possibility of a feed-forward mechanism involving cytosolic and mitochondrial ROS, although the mechanisms involved remain to be determined.…”
Section: Discussionmentioning
confidence: 97%
“…3, D and E). Interestingly, Nox4 protein has been reported to localize to the mitochondria in the right ventricles of a mouse model of pressure overload pulmonary hypertension (14) and in breast epithelial cells (17). These data suggest the possibility of a feed-forward mechanism involving cytosolic and mitochondrial ROS, although the mechanisms involved remain to be determined.…”
Section: Discussionmentioning
confidence: 97%
“…Emerging evidence show that mitochondria-generated ROS and cytosolic ROS (for example, NOX-generated ROS) interact with each other and may enhance the total cellular ROS production [88]; or some NOX isoforms may locate in mitochondria and become a source of mitochondrial ROS in addition to the ROS generated by electron transport complexes [89]. …”
Section: The Potential Role Of Ros In Melanoma Drug Resistancementioning
confidence: 99%
“…Recent studies showed that Nox4 mediated oxidative stress is a major cause in the failing heart [8], diabetic cardiomyopathy [39] and hypercholesterolemia induced cardiac dysfunction [40] and pressure overload pulmonary hypertension [41]. Thus, Nox4 mediated oxidative stress could be one of the possible mechanisms associated with acute F -induced cardiac dysfunction.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%